'A Measure of Autonomy': Federalism as Protection for Malaysia's Indigenous Peoples. (December 2018) - Harding, Andrew
This article is a case study of federalism in Malaysia as applied to the East Malaysian states of Sabah and Sarawak, which joined the federation in 1963. It is only in the case of these two states, in the context of Malaysia, that federalism is designed to deal with ethnic issues, the majority in both states being Indigenous people. Protection of these states' Indigenous people was a priority in 1963 and special status was given to these states in order to provide such protection. The study finds, nonetheless, that this special status has been eroded over the last 55 years by political interference by the federal government, and that the special status of these two states has proved ineffective, and indeed largely unacknowledged at the federal level. Accordingly, this study finds that federalism as protection for Indigenous people has been ineffective and the situation of the Indigenous people has as a result deteriorated over time. The solution, it is suggested, is through democratic empowerment at the state level and for federalism to provide deeper forms of constitutional protection.